Perception of quantity surveyors advising on building specifications to support sustainable building developments - Koigi, Stephen (Department of Construction Economics and Management, 2018)
Purpose: This research investigates the role and perceptions of quantity surveyors experienced with sustainable building projects and how they are able contribute as well as influence designs to address sustainability issues on projects. Design: To determine the considerations that affect quantity surveyors' perceptions towards sustainability in the construction industry, a literature review was carried out. This was followed by the development of an online survey formed of both structured and semi-structured questions that were issued out to South African quantity surveyors. This study administers online surveys distributed online to quantity surveyors on the ASAQS and the Green Building Council database consisting of 1499 registered members and 59 members respectively. Furthermore, in depth interviews were carried out with four quantity surveyors who had experience with green building projects. Findings: South Africa is accustomed to traditional building methods and the adoption of and adaptation to alternative building techniques is challenging to implement in the industry. The main barriers to sustainable building designs were the perceived higher cost of the materials as well as the lack of training and knowledge consultants have on material choices. Quantity surveyors nevertheless regarded the early design stages of a construction project as an ideal avenue for contribution towards sustainable building designs. Based on interviews conducted, professional quantity surveyors with experience on green building projects were more likely to contribute towards sustainable building specifications due to lessons learnt and knowledge from previous projects. However, quantity surveyors believed they generally have little influence towards green building specifications as the client and architect have the final say on what is incorporated into a building. Practical implications: The research study has provided a greater understanding of the role played by cost consultants on sustainability projects and how they can provide value to clients on such projects. Conclusions and Recommendations: The research concludes that Quantity surveyors are aware that they play a minor role player on project teams when it comes to providing alternative building specifications. It was acknowledged that quantity surveyors have limited experience on sustainable technologies and that further training and education in this regard is essential for them to add value to projects. It is recommended that further research be undertaken to obtain a larger sample size to get a clearer view of the perception of quantity surveyors advising on building specifications to support sustainable building developments.